A new genus and species of Nothochrysinae (Neuroptera: Chrysopidae) from the early Eocene Fur Formation, Denmark - Makarkin, Vladimir N.; Simonsen, Thomas J.; Perkovsky, Evgeny E. (Zootaxa, 2025)
Triachrysa rusti gen. et sp. nov. (Neuroptera: Chrysopidae: Nothochrysinae) is described from the earliest Eocene Fur Formation of Denmark. The three gradate series of crossveins in the forewing distinguishes the new genus from other Nothochrysinae known from this formation. The forewing venation is compared to that of three other genera of Nothochrysinae with three gradate series: the early Eocene Okanaganochrysa Makarkin & Archibald, 2013, the latest Eocene Tribochrysa Scudder, 1883, and the extant Triplochrysa Kimmins, 1952. These four genera are apparently not closely related, and their third (additional) series may have developed independently in these taxa.